Prevalence and associated comorbidities of body mass index ranges - Kaur, Jaspinder; Singh, Sargun; Kaur, Kawaljit (International Journal of Medicine, 2015)
Obesity is a global preventable epidemic inundating health care resources by increasing mortality and morbidity. The present study aimed to determine prevalence, risk factors, and co-morbidities associated with body mass index (BMI) ranges. A cross-sectional study was conducted to assess physical activity, dietary habits, alcohol, family history, sleep, stress, gender, age, education, employment and socioeconomic status as determinants of BMI. Total prevalence of overweight and obesity was reported among 33.34% and 18.24% of subjects, respectively; which increases with age (76.55%) and declines thereafter (21.87%). Female gender, primary and secondary education, middle social class, unemployment, positive family history, physical inactivity (p<0.001), non-vegetarian diet (p<0.05), adequate sleep, and significant stress was found associated with overweight and obesity. The prevalence of hypertension (p<0.05), hyperglycaemia (p<0.05), and hyperlipidemia was found directly proportional to increase in BMI. A rapidly rising obesity and its associated co-morbidities show that almost all the factors were potentially modifiable and preventable through lifestyle modification, which includes Dietary Approach to Stop Hypertension, daily 30minutes moderate-intensity physical activity and stress management.